PENERIMAAN DAN RESISTENSI TERHADAP KEBIJAKAN PENATAAN TRANSPORTASI ANGKUTAN UMUM DI KOTA BANDUNG - Arif Moelia Edie (Program Studi Manajemen Keamanan dan Keselamatan Publik IPDN, 2020)
This study aims to explain the implementation of public transportation management policies by the Bandung City Government, particularly from the perspective of public acceptance and resistance to government policies. With a qualitative research design, it was found that the policy implementation encountered obstacles of low enthusiasm and less public acceptance. The policy does not create new substantial things, so people consider it only to replace the old situation. As a result, the process of change is slow, and it only becomes a circular and incremental change. To improve the policy, it is necessary to make binding rules in the form of mayor regulations on minimum standards for public transport services and regional regulations on transportation development master plans as guidelines in restructuring public transport routes so that they do not overlap. Keywords: Policy Implementation; Public Acceptance; Public Resistance; Public Transportation Arrangement